Southern exposure : modern Japanese literature from Okinawa - Molasky, Michael S., 1956-; Rabson, Steve, 1943- (University of Hawai'i Press, 2000)
Southern Exposure is the first anthology of Okinawan literature to appear in English translation. It includes a wide range of fiction as well as a sampling of poetry from the 1920s to the present day.